"I'm an American Soldier": Country Music's Envoicing of Military Men and Families after 9/11. Issue 1 (2nd January 2019) - Decker, Todd
ABSTRACT: Toby Keith's number one hit "American Soldier" (2003) initiated a decade-long exploration of soldier-related topics by country music songwriters and singers, including forty-two tracks recorded between 2003 and 2014. Twenty-five records in this corpus were released as singles for radio play, with almost one-third of these reaching the top three positions on various country charts. Shared musical traits among the forty-two include a moderate tempo and a spare texture foregrounding the singer. The lyrics consistently feature soldiers, their families, and friends speaking in first person "I" voices. The implied "you" addressed by these "I" voices delimits the expressive scope of the corpus, at times hailing listeners beyond the country music audience, but primarily reaching out to the closest family and friend relations, with the resulting dialogue among intimates overheard by the sympathetic listener. Released mostly during the United States' invasion of Iraq and at the height of American soldier deaths in that conflict, country soldier songs only rarely engage with the fraught domestic politics of the war. Across the corpus of tracts, the celebration of victory proves out of reach. This body of melodramatic and mournful meditations on an ongoing and difficult war presents individuals and families dealing privately—in neoliberal fashion—with their grief.